2014
DOI: 10.1353/gpr.2014.0016
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Affordability and Access in Nebraska after the Great Recession

Abstract: The economic fallout from the Great Recession has not been experienced similarly across the United States. Therefore, our understanding of well-being is enhanced by analyzing state-level data. This study employs survey data of Nebraskans compiled shortly after the recession to assess factors affecting healthcare affordability and access. Findings show that the affordability of health care for households is significantly affected by income (i.e., as income increases, problems with affordability decrease) and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Having faced widespread rural hospital closures (28) and workforce shortages (99,130), rural health care systems lack the capacity to serve local residents (30,102,124,147). As a result, rural residents face long travel times that are difficult to manage because of employment and family responsibilities and few public transportation options.…”
Section: Community Factorsmentioning
confidence: 99%
“…Having faced widespread rural hospital closures (28) and workforce shortages (99,130), rural health care systems lack the capacity to serve local residents (30,102,124,147). As a result, rural residents face long travel times that are difficult to manage because of employment and family responsibilities and few public transportation options.…”
Section: Community Factorsmentioning
confidence: 99%
“…Besides income sources, it also depends on other sources such as savings, borrowings and other mechanisms to finance the health needs [ 16 ]. Snowden found that the affordability of health care for households was significantly affected by income, as income increased, problems with affordability decreased [ 17 ]. Montu and Somdutta thought that the richest class of the rural sector had the highest utilization of public healthcare facilities and the poorest class had the lowest utilization [ 18 ].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…In terms of the consumption environment, the imbalanced interaction between market suppliers, imperfect service supply system, and asymmetry of consumption information have severely increased the actual burden of older adults to use healthcare services, which results in an imbalance between the supply and demand and low realized utilization of healthcare services. Therefore, we take age, education level, psychosocial status, residence, self-assessed health status and gender as control variables [ 17 , 21 ], which can ensure that the results are not affected by individual characteristics. Among them, the psychosocial status refers to the attitudes and emotions of the elderly in facing different physical conditions, economic conditions, and life situations [ 34 ].…”
Section: Data and Variablesmentioning
confidence: 99%